Integrasi Fungsi Manajemen Pendidikan dalam Kepemimpinan Pendidikan Modern untuk Peningkatan Mutu Sekolah (Studi Kasus di SMP Negeri 1 Sukatani Purwakarta) - Aries Rapelianto; Patoni; Sany Rahmah Padilah; Deding Ishak; Deti Rostini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to analyze the integration of educational management functions into modern educational leadership to improve school quality at SMP Negeri 1 Sukatani Purwakarta. The study employed a qualitative approach using a case study method. Data were collected through interviews, observations, and document analysis involving the principal, vice principal, teachers, and supporting school documents. Data were analyzed through data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings revealed that educational planning was conducted collaboratively by developing school programs based on institutional needs and previous evaluation results. The implementation of management functions was supported by a clear division of responsibilities, continuous coordination, teacher professional development, and the implementation of the Merdeka Curriculum. Evaluation was carried out systematically through academic supervision, learning assessment, program monitoring, and follow-up actions based on evaluation results. The integration of planning, implementation, and evaluation functions within the principal’s leadership established a collaborative, adaptive, and quality-oriented school management system. The findings indicate that modern educational leadership plays a crucial role in integrating educational management functions, thereby enhancing the effectiveness of school management and improving the quality of educational services. Keywords: educational management functions, modern educational leadership, school quality, educational management.